A carbon-based surface light-trapping structure photothermal material and its construction method and application
By loading polyaniline on the surface of the carbon material and etching at high temperature, forming a trapped light structure, the problem of low photothermal conversion efficiency of existing carbon fiber and graphite sheets is solved, and efficient photothermal performance improvement and simple preparation process are achieved.
Patent Information
- Application Number
- CN202411345933.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The smooth surface and flat structure of existing carbon fiber and graphite sheets limit their photothermal conversion efficiency, and the preparation methods of existing carbon-based photothermal materials are complex, requiring simple and effective preparation methods to improve photothermal performance.
Polyaniline is loaded on the surface of the carbon material by electrochemical deposition, and soaked in a metal ion solution, and high-temperature etching is performed in a tube furnace to form a carbon-based photothermal material with a surface trapped light structure to regulate the pore size and depth , improve light absorption and light-thermal conversion performance.
It significantly improves the photothermal conversion performance of carbon materials, with absorbance reaching 93%-98% in the wavelength range of 300-2500nm, and the photothermal conversion temperature can reach 178℃. It also provides a simple preparation method, which enhances the ability of the material. Controlled.
Smart Images

Figure CN118847481B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal materials, and specifically relates to a photothermal material with a carbon-based surface light-trapping structure and a construction method and application thereof. Background Art
[0002] As an easily available renewable clean energy, solar energy can directly provide heat energy for human life or production through the photothermal conversion process. It is a supplementary energy source to enrich the application energy structure and alleviate energy shortage. As an important material for photothermal conversion, carbon materials have the advantages of a wide range of raw material sources and excellent thermal conductivity, and have broad application prospects. However, carbon materials still face some challenges and problems at the current stage. The structure and morphology of carbon fiber and graphite sheets have an important influence on their photothermal performance, including the control of their surface morphology and microstructure. The existing carbon fiber and graphite sheets on the market mostly have smooth surfaces and flat structures, which are not conducive to the absorption-photothermal conversion process, and the photothermal conversion efficiency is low, which limits the further improvement of their photothermal conversion performance. In addition, the preparation method and processing technology of existing carbon-based photothermal materials are relatively complex, relying on precise processes and professional equipment processing, and it is necessary to find a more economical and effective preparation method. This patent constructs a carbon-based photothermal material with a surface light-trapping structure through a simple technical method, adjusts the pore size and depth, changes its surface morphology and microstructure, and prepares a carbon-based photothermal material with high photothermal conversion performance. Summary of the invention
[0003] The purpose of the present invention is to provide a carbon-based surface light-trapping structured photothermal material and a method and application of its construction to solve the problems existing in the prior art.
[0004] A method for constructing a carbon-based surface light-trapping structure photothermal material comprises: loading polyaniline on the surface of the carbon material by electrochemical deposition, then immersing it in a metal ion solution, washing and drying it, and then placing it in a tubular furnace for high-temperature etching at 800-1000°C for 4-8 hours in an inert gas atmosphere.
[0005] Further, the following steps are included:
[0006] (1) Treat the carbon material with acid and then wash it with deionized water;
[0007] (2) The surface of the carbon material treated in step (1) is loaded with 0.03-0.06 mg cm -2 of polyaniline;
[0008] (3) The carbon material with polyaniline loaded on the surface obtained in step (2) was immersed in a 0.1 mol·L -1 -1mol·L -1 Place in metal ion solution for 12-24 hours, remove, wash and dry;
[0009] (4) Placing the carbon material in a tube furnace and etching it at 800-1000°C for 4-8 hours in an inert gas atmosphere to form a light-trapping structure containing metal nanoparticles with a surface roughness and a pore size of 20-500 nm and a pore depth of 0.1-1 μm.
[0010] Furthermore, the step (2) of loading polyaniline on the surface of the treated carbon material comprises: placing the treated carbon material in the step (1) in a liquid having a pH of 1 and a concentration of 0.1 mol·L -1 -1mol·L -1 In the aniline electrolyte, a graphite rod was used as the counter electrode, a carbon material was used as the working electrode, and Ag / AgCl was used as the reference electrode. The cyclic voltammetry method was used and the voltage range was set to 0.5-1.5 V. During the electrolysis process, aniline was added to the p-toluenesulfonic acid solution with an aniline concentration of 0.1 mol·L -1 -1mol·L -1 , and then adjust the pH to 1.
[0011] In the present invention, the surface of the carbon material treated in step (2) can be loaded with polyaniline by spraying or dripping, specifically comprising: adding 0.1 mol·L -1 -0.2mol·L -1 Aniline solution and 0.5 mol·L -1 -1mol·L -1 After the hydrochloric acid solution is evenly mixed, an ammonium persulfate solution (the molar ratio of ammonium persulfate to aniline is 0.5-2:1) is added dropwise, and the polyaniline solution is obtained by reacting at 2-4°C for 10-12h. Finally, the polyaniline solution is evenly sprayed or dripped onto the surface of the carbon material, wherein the sprayed or dripped polyaniline loading is 0.03-0.06 mg·cm -2 .
[0012] Furthermore, the concentration of the metal ion solution is 0.1 mol·L -1 -1mol·L -1 .
[0013] Furthermore, the metal solution includes one or more of ferric nitrate solution, cobalt nitrate solution, nickel nitrate solution, cobalt acetate solution, cobalt acetylacetonate solution, ferric acetylacetonate solution, ferric chloride solution, cobalt chloride solution, and nickel chloride solution.
[0014] Furthermore, the mass ratio of the carbon material to the metal ion solution is 0.1-0.5:1.
[0015] The carbon-based surface light-trapping structure photothermal material constructed by the above construction method includes a carbon material with a surface light-trapping structure and metal nanoparticles loaded on the surface of the carbon material.
[0016] Furthermore, the surface light-trapping structure constructed on the surface of the carbon material has a pore size of 20-500nm, a pore depth of 0.1-1μm, and an absorbance of more than 90% in the 300-2500nm band.
[0017] The above-mentioned photothermal materials are used for interfacial water evaporation, photothermal power generation, photothermal sterilization, etc.
[0018] The present invention etches the surface of the carbon material with metal at high temperature to increase its surface roughness and form a surface light-trapping structure with high-efficiency light-absorbing properties, which can effectively improve the photothermal performance of the carbon material and provide a simple and universal method for constructing the surface light-trapping structure of carbon-based photothermal materials, providing a useful reference for the research and development of high-performance carbon-based photothermal materials.
[0019] Polyaniline has good adsorption properties for metal ions. After loading polyaniline on the surface of carbon materials and then adsorbing metal ions, the adsorption of metal ions can be regulated, thereby realizing the regulation of the concentration of metal ions on the surface of carbon-based materials, so that the size of carbide / metal nanoparticles formed during high temperature can be accurately controlled, thereby enhancing the accuracy of controlling the etching of carbon-based surfaces by metal ions. In addition, polyaniline loaded on the surface of carbon-based materials is more likely to decompose and form carbide / metal particles with metal ions under high temperature conditions, which is beneficial to protect the carbon-based surface during high temperature etching, making the etching of carbon-based surfaces more controllable.
[0020] Metal ions are the key to etching the surface of carbon materials. During the high-temperature carbonization process in a tubular furnace, metal ions etch the surface of carbon materials by reducing metal atoms, forming carbides, and decomposing into metals. By regulating the concentration and temperature of metal ions, the surface roughness of carbon materials can be regulated, and pore structures of different sizes and depths can be formed on the surface of carbon materials, thereby constructing a light-trapping structure.
[0021] The surface roughness of the carbon material obtained by the present invention is increased, and many holes of different sizes and depths are formed on the surface. The defect structure is only formed on the surface, which not only retains the complete structure of the carbon material itself, but also constructs a light-trapping structure on the surface. A large number of holes are conducive to the formation of multiple refractions inside the material after absorbing sunlight, thereby improving the light absorption performance of the material. The absorption rate of the light-trapping structure of the carbon material of the present invention is significantly improved, and the absorbance can reach 93%-98% within the wavelength of 300-2500nm. The photothermal conversion temperature of the carbon material is greatly improved compared with the initial carbon material, at 484 mW / cm -2 Under high light intensity, the photothermal conversion temperature can reach about 178°C.
[0022] After polyaniline is loaded on the surface of the carbon material, the present invention allows metal ions to be adsorbed on the surface of the carbon material, and a light trapping structure on the surface of the carbon material is constructed by high-temperature etching. Most existing processes use metals to form a composite structure with carbon materials, while the present invention uses high-temperature metal etching to construct a new structure.
[0023] Compared with the prior art, the present invention loads polyaniline on the surface of the carbon material by electrochemical deposition, and adsorbs metal ions on the surface of the carbon material by immersion adsorption, and then places it in a tubular furnace and performs high-temperature etching in an argon atmosphere. The surface roughness of the carbon material can be regulated by regulating the concentration and temperature of the metal ions to construct a light-trapping structure. The present invention prepares a photothermal material that effectively promotes the light absorption-photothermal conversion process, which can effectively increase the material's ability to absorb sunlight and convert light energy into thermal energy. The absorption rate is significantly improved, and the absorbance can reach 93%-98% within a wavelength of 300-2500nm. The photothermal conversion temperature of the carbon material is greatly improved compared to the initial carbon material, at 484 mW / cm -2 Under high light intensity, the photothermal conversion temperature can reach about 178°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The photothermal conversion performance test of the photothermal material constructed with the light trapping structure on the surface of the carbon material obtained in Examples 1-3;
[0025] Figure 2 This is an elemental analysis diagram of the carbon fiber loaded with polyaniline and adsorbed with Fe ions according to Example 1 of the present invention;
[0026] Figure 3 It is a photothermal material surface defect morphology image constructed by a carbon material surface light trapping structure prepared with carbon fiber as carbon material;
[0027] Figure 4 It is the surface defect morphology of the photothermal material constructed by the light trapping structure on the surface of the carbon material prepared by the carbon fiber graphite plate;
[0028] Figure 5 It is the ultraviolet-visible-near infrared spectrum of the photothermal material constructed by the light trapping structure on the surface of the carbon material of the present invention;
[0029] Figure 6 The photothermal material constructed by the carbon material surface light trapping structure of the present invention has an output power of 484 mW / cm -2 Photothermal conversion performance diagram under light intensity;
[0030] Among them, CFs is the initial carbon material, and 1.0-1000 represents the photothermal material obtained by using 1.0M Fe metal ions and calcining at 1000°C. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0032] Example 1
[0033] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0034] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0035] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 800°C at a rate of 1.18°C and maintained at 800°C for 240 minutes.
[0036] Example 2
[0037] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0038] Prepare 100mL 1 mol·L -10.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0039] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 900 °C at a rate of 1.1 and maintained at 900 °C for 240 min.
[0040] Example 3
[0041] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0042] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0043] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0044] Example 4
[0045] The carbon fiber felt was cut into a shape of 5 cm in length, 5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0046] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0047] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0048] Example 5
[0049] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0050] Prepare 100mL 1 mol·L -10.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0051] Prepare 0.5 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0052] Example 6
[0053] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0054] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0055] Prepare 0.5 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 900 °C at a rate of 1.1 and maintained at 900 °C for 240 min.
[0056] Example 7
[0057] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0058] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0059] Prepare 0.5 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 800 °C at a rate of 1.1 and maintained at 800 °C for 240 min.
[0060] Example 8
[0061] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0062] Prepare 100mL 1 mol·L -10.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0063] Prepare 0.1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0064] Example 9
[0065] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0066] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0067] Prepare 0.1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 900 °C at a rate of 1.1 and maintained at 900 °C for 240 min.
[0068] Example 10
[0069] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0070] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0071] Prepare 0.1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 800 °C at a rate of 1.1 and maintained at 800 °C for 240 min.
[0072] Embodiment 11
[0073] The hydrophilic carbon fiber cloth was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 0.5 mm in thickness, and washed with ethanol and deionized water in sequence. The washed hydrophilic carbon fiber cloth was placed in sulfuric acid, with a graphite rod as the counter electrode, the hydrophilic carbon fiber cloth as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The hydrophilic carbon fiber cloth was acid treated for 10 minutes and then washed with deionized water.
[0074] Prepare 100mL 1 mol·L -10.925 mL of p-toluenesulfonic acid solution was added thereto, and then hydrochloric acid was used to adjust the pH to 1. The treated hydrophilic carbon fiber cloth was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the hydrophilic carbon fiber cloth as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the hydrophilic carbon fiber cloth for 50 cycles.
[0075] Prepare 1 mol·L -1 The loaded hydrophilic carbon fiber was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried hydrophilic carbon fiber was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0076] Example 12
[0077] The hydrophobic carbon fiber cloth was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 0.5 mm in thickness, and washed with ethanol and deionized water in sequence. The washed hydrophobic carbon fiber cloth was placed in sulfuric acid, with a graphite rod as the counter electrode, the hydrophobic carbon fiber cloth as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The hydrophobic carbon fiber cloth was acid treated for 10 minutes and then washed with deionized water.
[0078] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added thereto, and then hydrochloric acid was used to adjust the pH to 1. The treated hydrophobic carbon fiber cloth was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the hydrophobic carbon fiber cloth as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the hydrophobic carbon fiber cloth for 50 cycles.
[0079] Prepare 1 mol·L -1 The loaded hydrophobic carbon fiber was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried hydrophobic carbon fiber was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0080] Example 13
[0081] The graphite sheet was cut into a shape of 2 cm in length, 2 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed graphite sheet was placed in sulfuric acid, with a graphite rod as the counter electrode, a graphite sheet as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The graphite sheet was treated with acid for 10 minutes, and then washed with deionized water.
[0082] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added thereto, and then hydrochloric acid was used to adjust the pH to 1. The treated graphite sheet was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, a graphite sheet as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, with the voltage range set to 0.5-1.5 V and the scan speed set to 0.05 V / s. Polyaniline was loaded on the surface of the graphite sheet for 50 cycles.
[0083] Prepare 1 mol·L -1 The loaded graphite sheet was immersed in the solution of FeCl3·6H2O for 12 h, then taken out, washed, and dried at 60°C. The dried graphite sheet was placed in a tube furnace and heated at 2.5°C·min under argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0084] Embodiment 14
[0085] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0086] Prepare 100mL 1 mol·L -10.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0087] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a CoCl2·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tube furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0088] Embodiment 15
[0089] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0090] Prepare 100mL 1 mol·L -1 0.925 mL of p-toluenesulfonic acid solution was added to it, and then hydrochloric acid was used to adjust the pH to 1. The treated carbon fiber felt was placed in the prepared aniline electrolyte, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The cyclic voltammetry method was used, the voltage range was set to 0.5-1.5 V, the scanning speed was 0.05 V / s, and polyaniline was loaded on the surface of the carbon fiber felt for 50 cycles.
[0091] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a Ni (NO3)2·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 1000 °C at a rate of 1.1 and maintained at 1000 °C for 240 min.
[0092] Example 16
[0093] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0094] Prepare 50 mL of 0.1 mol·L -1 Aniline solution and 50 mL 0.5 mol·L -1 After the hydrochloric acid solution is mixed evenly, the ammonium persulfate solution (the molar ratio of ammonium persulfate to aniline is 0.5:1) is added dropwise and reacted at 2-4°C for 10-12h to obtain the polyaniline solution. The polyaniline solution is then evenly sprayed or dripped onto the surface of the carbon material (the sprayed polyaniline loading is 0.03mg·cm -2 ).
[0095] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 800°C at a rate of 1.18°C and maintained at 800°C for 240 minutes.
[0096] Embodiment 17
[0097] The carbon fiber felt was cut into a shape of 1.5 cm in length, 1.5 cm in width, and 2 mm in thickness, and washed with ethanol and deionized water in sequence. The washed carbon fiber felt was placed in sulfuric acid, with a graphite rod as the counter electrode, the carbon fiber felt as the working electrode, and Ag / AgCl (saturated KCl) as the reference electrode. The it method was used, and the voltage was set to 1.6V (vs Ag / AgCl (saturated KCl)). The carbon fiber felt was treated with acid for 10 minutes and then washed with deionized water.
[0098] Prepare 50 mL of 0.2 mol·L -1 Aniline solution and 50 mL 1.0 mol·L -1After the hydrochloric acid solution is mixed evenly, the ammonium persulfate solution (the molar ratio of ammonium persulfate to aniline is 2:1) is added dropwise and reacted at 2-4°C for 10-12h to obtain the polyaniline solution. The polyaniline solution is then evenly sprayed or dripped onto the surface of the carbon material (the sprayed polyaniline loading is 0.06mg·cm -2 ).
[0099] Prepare 1 mol·L -1 The loaded carbon fiber felt was placed in a FeCl3·6H2O solution and immersed in the solution for 12 h, then taken out, washed, and dried at 60 °C. The dried carbon felt was placed in a tubular furnace and heated at 2.5 °C·min under an argon atmosphere. -1 The temperature was raised from room temperature to 800°C at a rate of 1.18°C and maintained at 800°C for 240 minutes.
[0100] Comparative Example 1
[0101] The carbon material was treated with acid according to Example 1, and then washed with deionized water; then the carbon material was directly immersed in a metal ion solution for 12-24 hours, taken out, washed, and dried; and placed in a tube furnace and etched at 800-1000° C. for 4-8 hours in an inert gas atmosphere. It was found that the metal nanoparticles could not be adsorbed on the surface of the carbon material.
[0102] Performance Testing
[0103] from Figure 1 It can be seen that the Fe 3+ The photothermal conversion performance of the carbon material with a light-trapping surface obtained by etching is significantly better than that of the carbon material with a smooth surface under full-spectrum xenon lamp irradiation, and the photothermal conversion performance of the photothermal materials obtained by etching at different temperatures is different.
[0104] from Figure 2 It can be seen that after polyaniline was loaded on the carbon fiber surface, the metal was successfully adsorbed on the carbon fiber surface.
[0105] The specific defect structure of the material is as follows Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the roughness of the carbon fiber surface increases, and many holes are formed on the surface, with different sizes and a pore range of 20-500nm. From the morphology of the material cross section, it can be seen that the defect structure is only formed on the surface, which not only retains the complete structure of the carbon fiber itself, but also constructs a light trapping structure on the surface. From the morphology of the graphite plate surface, it can be seen that the flat surface of the graphite plate is changed, forming a large number of pore structures of varying depths, and the pore depth range is 0.1-1μm.
[0106] The performance advantages of the material are mainly reflected in good light absorption and excellent light-to-heat conversion performance. Currently, three metals, Fe, Co, and Ni, have been tried, and they can all improve the light-to-heat conversion performance of carbon fiber, but under the same conditions, Fe has the best effect. Figure 5 It can be seen that the absorption rate of the light trapping structure of the carbon material of the present invention is significantly improved compared with the initial carbon fiber, and the absorbance can reach 93%-98% within the wavelength range of 300-2500nm. Figure 6 It can be seen that the photothermal conversion temperature of the carbon material is greatly improved compared with the initial carbon fiber, at 484 mW / cm -2 Under the light intensity, the photothermal conversion temperature can reach about 178°C. It can be concluded that the light trapping structure of the carbon material effectively increases the material's ability to absorb sunlight and convert light energy into heat energy.
[0107] The present invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. A method for constructing a photothermal material with a carbon-based surface light-trapping structure. It is characterized in that include: (1) Treat the carbon material with acid and then wash it with deionized water; (2) The surface of the carbon material treated in step (1) is loaded with 0.03-0.06 mg cm -2 Polyaniline; (3) The carbon material with polyaniline on the surface obtained in step (2) was immersed in a solution with a concentration of 1 mol·L -1 Place in metal ion solution for 12-24 hours, remove, wash and dry; (4) placing the carbon material in a tube furnace and etching it at 1000°C for 4-8 hours in an inert gas atmosphere to form a light trapping structure containing metal nanoparticles and having a pore size of 20-500 nm and a pore depth of 0.1-1 μm on the surface of the carbon material; The metal ion solution in step (3) includes one or more of ferric nitrate solution, ferric acetylacetonate solution, and ferric chloride solution; the mass ratio of the carbon material to the metal ion solution is 0.1-0.5:
1.
2. The construction method according to claim 1, It is characterized in that The carbon material includes carbon fiber and graphite plate.
3. The construction method according to claim 1, It is characterized in that The surface loading of the carbon material treated in step (2) is 0.03-0.06 mg cm -2 Polyaniline includes: 0.1 mol·L -1 -0.2mol·L -1 Aniline solution and 0.5 mol·L -1 -1mol·L -1 After the hydrochloric acid solution is evenly mixed, the ammonium persulfate solution is added dropwise, and the mixture is reacted at 2-4° C. for 10-12 hours to obtain a polyaniline solution. Finally, the polyaniline solution is evenly sprayed or dripped onto the surface of the carbon material treated in step (1).
4. A carbon-based photothermal material with a surface light trapping structure constructed according to the construction method according to any one of claims 1 to 3, comprising a carbon material with a surface light trapping structure and metal nanoparticles loaded on the surface of the carbon material.
5. The photothermal material with a carbon-based surface light-trapping structure according to claim 4, It is characterized in that The absorbance of the surface light-trapping structure of the carbon material in the 300-2500nm band is greater than 90%.
6. The photothermal material with a carbon-based surface light-trapping structure according to claim 4, It is characterized in that The metal nanoparticles are Fe.
7. Application of the photothermal material with a carbon-based surface light-trapping structure according to claim 4, It is characterized in that Used for interfacial water evaporation, photothermal power generation and photothermal sterilization.
Citation Information
Patent Citations
Preparation method and application of photo-thermal catalyst
CN117654492A
